Knowledge of Nurses Toward Covid-19 at Primary Health Care - Mansour Abdullah Falah (Kufa Journal for Nursing Sciences)
Background: Nurses' COVID-19 knowledge in primary health care is vital for managing the pandemic, including prevention, detection, and patient education. As we know, the danger of Covid-19 is not limited to workers in health centers only, but it may develop and spread to all members of society due to the lack of knowledge of health workers about methods of prevention and protection from this disease.